2009
DOI: 10.1159/000217586
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Buprenorphine Maintenance Therapy Programs in the Ukraine: First Promising Treatment Outcomes

Abstract: Background: Opiate substitution therapy (OST) in the Ukraine was not provided until 2004. As part of the introduction of OST, the first feasibility study was conducted in 2007. Six clinics in 6 cities were involved in providing OST and collecting data. Methods: A total of 151 opiate-dependent patients were given buprenorphine as a substitute, and a survey of substance use, HIV transmission risks, and legal and social status was conducted at baseline and at 6 and 12-month follow-up. Results: Illegal substance u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Hans-Ulrich Wittchen et al found that the retention rate in Germany at 12 months was 75% [13]. Six-month treatment retention rates observed in our study were similar to those found by Ukrainian researchers [14, 15]. Such differences could be explained by the different methodology used in different studies.…”
Section: Discussionsupporting
confidence: 87%
“…Hans-Ulrich Wittchen et al found that the retention rate in Germany at 12 months was 75% [13]. Six-month treatment retention rates observed in our study were similar to those found by Ukrainian researchers [14, 15]. Such differences could be explained by the different methodology used in different studies.…”
Section: Discussionsupporting
confidence: 87%
“…This is despite evidence from several systematic reviews suggesting that: PWID who receive OST have less than half the risk of HIV infection compared with PWID not on OST (MacArthur et al, 2012); OST is associated with greater adherence to ART (Malta, Magnanini, Strathdee, & Bastos, 2010); OST is associated with reductions in illicit opioid use, injecting behaviour, and sharing of injection equipment (Gowing, Farrell, Bornemann, Sullivan, & Ali, 2011); and OST is associated with a reduction by more than half in all-cause mortality among PWID (Degenhardt et al, 2011). These international findings have also been confirmed in studies conducted specifically in Ukraine (Bachireddy et al, 2013; Lawrinson et al, 2008; Schaub, Chtenguelov, Subata, Weiler, & Uchtenhagen, 2010; Schaub, Subata, Chtenguelov, Weiler, & Uchtenhagen, 2009). Additionally, modelling data suggesting that expanding harm reduction services, including OST, and access to ART are the most cost-effective methods of controlling the HIV epidemic in Ukraine (Alistar, Owens, & Brandeau, 2011).…”
Section: Introductionsupporting
confidence: 63%
“…Critically, provision of this treatment is minimal in many of the countries with highest prevalence of HIV in people who inject drugs,66 67 and treatment for opiate dependence with methadone remains illegal in Russia 58. Increased coverage in many of these countries,15 24 25 however, is a welcome advance.…”
Section: Discussionmentioning
confidence: 99%
“…Opiate substitution treatment has been implemented in 70 countries, but remains unavailable in 66, and in several countries detoxification or residential rehabilitation is the primary mode of treatment 223 Although coverage of opiate substitution treatment is being expanded in some countries, such as Ukraine, India, and China,24 25 26 intervention at a regional and national level remains poor in many countries, including those with a high burden of HIV among people who inject drugs 23…”
Section: Introductionmentioning
confidence: 99%